Fumaric Acid in Broiler Nutrition: A Dose Titration Study and Safety Aspects - Islam, K.M.S.; Schuhmacher, A.; Aupperle, H.; Gropp, J.M. (International Journal of Poultry Science, 2008)
Six isonitrogenous (22.8% CP) and isocaloric diets (13 MJ ME/kg) containing 0, 1.25, 2.50, 3.75, 5.0 and 7.5% fumaric acid (FA), respectively, were fed for 26 days to 12 (replicates) x 8 (chicks per replicate) Lohmann-Hybrid newly hatched male chicks (48 g body weight) per treatment. The diets consisted mainly of wheat and soybean meal. Mortality ranged between 0 and 4 %. Final body weight (and feed efficiency) amounted to 1,506 (756), 1,597 (767), 1,532 (754), 1,485 (759), 1,342 (738) and 1,378 g (747 g gain/kg feed) for the groups with 0, 1.25, 2.50, 3.75, 5.0 and 7.5% FA, respectively. The 1.25% FA group showed significantly (p